A Content Analysis on Quality for Cad Based Product Design: Developing a Framework for Malaysian Technical Teacher Training Institute - Saleh, Baharudin; Rasul, Mohamad Sattar; Mohd Affandi, & Haryanti (Journal of Technical Education and Training, 2019)
Product design is a complicated process and requires a systematic requirement and specification to produce sufficient quality to remain competitive. One of the most important components in the design process is Computer-Aided Design (CAD), which renders a detailed drawing in either two-dimensional (2D) or three-dimensional modeling (3D). This paper discusses the conception of quality design to produce a creative design product. This study employed a systematic review to produce a framework of quality product design based on Computer-Aided Design (CAD). Out of 210 papers that were identified, 102 were reviewed and also 12 other relevant articles, books, reports, and documents, hence a total of 114 papers were included in this review. The reviews revealed that there are main aspect drivers of the product design, design process, design quality, customer need on the product, product evaluation, and design concept of quality products. The study also showed that the initial stage of idea-generating is an essential phase to produce innovative, creative and quality product design. This framework is useful as a guide for teachers to standardize product design concept and to assist Malaysian design and technology trainee teachers in producing a quality product design. Finally, this research proposes a conceptual framework based on our propositions. The proposed quality product design framework is beneficial to be used as a guideline for the Malaysian Technical Teacher Training Institute and policy makers to enhance the skills in the development of a quality product.